2013
DOI: 10.1371/journal.pone.0065655
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological Characteristics of Lower Extremity Cellulitis after a Typhoon Flood

Abstract: ObjectiveThe flood after a typhoon may lead to increase in patients with cellulitis of lower limbs. However, the microbiological features of these cases are rarely reported. We conducted a study of patients with lower extremity cellulitis after a typhoon followed in southern Taiwan to study the risk factors of cellulitis and the bacteriological features of the patients.MethodsWe reviewed all the medical records of cellulitis at emergency departments of two teaching hospitals in southern Taiwan 30 days before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…This is consistent with previous studies which found that inflammatory skin diseases, skin infections, traumatic skin diseases, insect bite reactions, and psycho-emotional aggravated primary skin diseases were common problems during floods. 12,13 Although the J-SPEED data don't allow to specify the exact type of skin diseases, it can still be suggested that skin disease is a common health problem not only in developing countries, but also in developed countries during heavy rain disasters. The current findings also revealed that skin disease is most common among children aged 0-8 years.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies which found that inflammatory skin diseases, skin infections, traumatic skin diseases, insect bite reactions, and psycho-emotional aggravated primary skin diseases were common problems during floods. 12,13 Although the J-SPEED data don't allow to specify the exact type of skin diseases, it can still be suggested that skin disease is a common health problem not only in developing countries, but also in developed countries during heavy rain disasters. The current findings also revealed that skin disease is most common among children aged 0-8 years.…”
Section: Discussionmentioning
confidence: 99%
“…94 Treatment Facility Presentations (%) Survey Responses (%) a Significant increases in impetigo, conjunctivitis, and cellulitis at treatment facilities were reported in the first two weeks after storms, 74,87 and the number of lower extremity cellulitis cases receiving treatment at ECFs increased during the first week after landfall (RR: 2.8; 95% CI, 2.0-2.4) compared to the control period. 95 However, one island-wide surveillance study of all treatment facilities found no increase in visits for skin infections in the week after a cyclone. 87 Eighteen cases of wound-associated Vibrio illness, linked to a hurricane, also were identified two weeks after landfall.…”
Section: Infectious and Parasitic Diseasesmentioning
confidence: 99%
“…In Brazil, the increased cases of focal retinal whitening and necrotizing retinochoroiditis identified in a flood have been associated with the Toxoplasma gondii infection in the contaminated water [ 13 ]. A study found patients with cellulitis of lower limbs after a severe flood 6.2-fold more likely to have immersed the limbs in the flood water than non-patients [ 3 ]. Fungal skin infection, bacterial skin infection, eczema, urticarial and scabies also have been associated with flood or hurricane [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%